ATTITUDE OF PLUS TWO STUDENTS TOWARDS PUBLIC EXAMINATION IN RELATION TO PARENTAL PRESSURE - Chrysolyte, S. Vinolin; Dharma Raja, B. William (International Journal of Research -GRANTHAALAYAH, 2016)
This study examines the attitude of plus two students towards public examination and its relationship with parental pressure. The sample of the study comprised of 386 plus two students from Tirunelveli district. The authors employed survey method for collecting the data and they were analysed using descriptive and inferential statistical techniques. It was found that there is a significant relation between the attitude of students towards +2 public examination and parental pressure.